(untitled) (Journal of Information Technologies in Education (ITE), 2013)
The article considers the legislative requirements and features of distribution of the pedagogical software, a condition of the market of this production in Ukraine; the main actions for sales promotion and the advertising, optimization of marketing communications for the pedagogical software developers.